Teachers’ Views of Children With Developmental Language Disorder in Greek Mainstream Schools - Ralli, Asimina M.; Kalliontzi, Eleni; Kazali, Elena (Frontiers in Education, 2022)
Within a modern school that follows the international rules of inclusive education is very important teachers to be able to understand and meet the needs of children with Developmental Language Disorder (DLD). The present study explores for the first time in Greece, the views of 122 Greek Kindergarten Teachers (KTs) and Primary school teachers (PSTs) about DLD, through an online survey that elaborated both categorical and Likert scale responses. According to the results half of the participants were not familiar with the term. Both groups of professionals reported that children with DLD have many vocabulary and syntactic difficulties in the receptive language. In the expressive language KTs identified more articulation and phonological difficulties, while PSTs referred mainly vocabulary and grammatical difficulties. The majority of professionals mentioned additional difficulties such as emotional and behavioral difficulties. Both groups identified a variety of challenges while working with children with DLD. KTs focused mostly on children’s emotional difficulties, while PSTs reported mostly their learning difficulties. The participants also recognized their own limitations regarding background knowledge and the need for further training. Furthermore, the educators mentioned that it is difficult for them to identify and support a child with DLD while, at the same time they acknowledged the need to collaborate with other professionals in order to meet children’s needs. The results are discussed in terms of their importance for raising awareness for DLD as well as for teachers’ better training, in order to efficiently identify and support children with DLD.